2023
DOI: 10.1021/acsami.2c19596
|View full text |Cite
|
Sign up to set email alerts
|

Junctionless Electric-Double-Layer MoS2 Field-Effect Transistor with a Sub-5 nm Thick Electrostatically Highly Doped Channel

Abstract: Junctionless transistors are suitable for sub-3 nm applications because of their extremely simple structure and high electrical performance, which compensate for short-channel effects. Two-dimensional semiconductor transition-metal dichalcogenide materials, such as MoS2, may also resolve technical and fundamental issues for Si-based technology. Here, we present the first junctionless electric-double-layer field-effect transistor with an electrostatically highly doped 5 nm thick MoS2 channel. A double-gated MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…17,19,32,33 For example, Jeon et al systematically investigated the volume and surface accumulation conduction of silicon junctionless transistors by demonstrating the doping concentration-dependent g m and dg m curves. 32 In addition, Balestra et al demonstrated the separation of surface and volume inversion in double-gate silicon-on-insulator transistors with respect to the top and bottom electrostatic gate potentials. 33 Seo et al examined the presence of top-and bottom-surface channels along the thickness in 2D vdW multilayers upon the observation of two plateaus in their transconductance curves.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,32,33 For example, Jeon et al systematically investigated the volume and surface accumulation conduction of silicon junctionless transistors by demonstrating the doping concentration-dependent g m and dg m curves. 32 In addition, Balestra et al demonstrated the separation of surface and volume inversion in double-gate silicon-on-insulator transistors with respect to the top and bottom electrostatic gate potentials. 33 Seo et al examined the presence of top-and bottom-surface channels along the thickness in 2D vdW multilayers upon the observation of two plateaus in their transconductance curves.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous theoretical calculations and experiments have reported that the variation in the shape and amplitude of g m and d g m behaviors are closely linked to the carrier transport mechanisms. ,,, For example, Jeon et al systematically investigated the volume and surface accumulation conduction of silicon junctionless transistors by demonstrating the doping concentration-dependent g m and d g m curves . In addition, Balestra et al demonstrated the separation of surface and volume inversion in double-gate silicon-on-insulator transistors with respect to the top and bottom electrostatic gate potentials .…”
Section: Resultsmentioning
confidence: 99%
“…and all are greater than the IRDS 2021 requirements for high performance (HP) technologies. It is also noted that for the p-type doping concentrations13 1.66 10  cm -2 ON-state performance is also satisfied for HD application benchmark requirements. Further, the JLFET performance not significantly affected by the variations in ds V in the ranges 0.03 0…”
mentioning
confidence: 79%
“…Furthermore, unlike few-layer MoS2, which typically displays n-type behavior, BP can be modulated into both p-type and n-type structures thanks to its rather small band gap. [13]. The phosphorus atoms in BP create a covalent bond with three nearby atoms, however unlike graphene, BP takes the form of a puckered structure with ridges that are not in the plane.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unlike few-layer MoS2, which typically displays n-type behavior, BP can be modulated into both p-type and n-type structures thanks to its rather small band gap. [13]. The phosphorus atoms in BP create a covalent bond with three nearby atoms, however unlike graphene, BP takes the form of a puckered structure with ridges that are not in the plane.…”
Section: Introductionmentioning
confidence: 99%